South African post-apartheid economic planning and performance: a critical assessment of GEAR - Mathebula, Sambulo Phiwokuhle Sabelo (My University, 2016)
The ANC ascended to government against the backdrop of a rapidly changing global political economic order after the end of the Cold War. This effectively marked the collapse of communism as a global political force and the concomitant dominance of neoliberalism. In 1996, the African National Congress government adopted the Growth Employment and Redistribution strategy (GEAR) as its new economic blue print, through which it would pursue its transformation agenda. In so doing, the ANC circumvented economic policy consultation processes with its political alliance partners and declared GEAR ‘non-negotiable’. This research argues that the shift to GEAR was essentially an economic policy alignment with the dominant post -Cold War neoliberal discourse and practice. It was fashioned deliberately by key ANC policy makers who had bought into the neoliberal assumption that development would occur after economic growth had been attained. The GEAR strategy privileged market led reforms which subordinated the transformation agenda to orthodox macroeconomic considerations. The pro-market bias which began with the adoption of the GEAR strategy has continued to shape South Africa’s post-apartheid economic policy environment to a significant extent.
Thesis submitted in partial fulfilment of the requirements for the degree of Masters in Arts in (Political Studies) University of the Witwatersrand February, 2015
Keywords: Economic development; South Africa--Economic policy; South Africa--Economic conditions